Omega‐3 fatty acids and/or fluvastatin in hepatitis C prior non‐responders to combination antiviral therapy – a pilot randomised clinical trial. (14th October 2013) - Sheridan, David A.; Bridge, Simon H.; Crossey, Mary M. E.; Felmlee, Daniel J.; Fenwick, Fiona I.; Thomas, Howard C.; Neely, R. Dermot G.; Taylor‐Robinson, Simon D.; Bassendine, Margaret F.
Abstract Background & Aims Hepatitis C virus (HCV) utilises cholesterol and lipoprotein metabolism for replication and infectivity. Statins and omega‐3 (n–3) polyunsaturated fatty acids (PUFA) have been shown to have antiviral properties in vitro. This open label pilot study evaluated the efficacy of fluvastatin (Lescol® 40–80 mg) and n‐3 PUFA (Omacor®1 g and 2–4 g) on HCV‐RNA and lipoviral particles (LVP) in difficult to treat prior non‐responders. Methods Patients (n = 60) were randomly allocated in a factorial design to: no active drug; low‐dose n‐3 PUFA; high‐dose n‐3 PUFA; fluvastatin; low‐dose n‐3 PUFA + fluvastatin; or high‐dose n‐3 PUFA + fluvastatin. 50/60 completed study drugs for 12 weeks and followed up to week 24. Comparison was made between fluvastatin (n = 24) vs no fluvastatin (n = 26) and n‐3 PUFA high‐dose (n = 17) vs low‐dose (n = 17) vs none (n = 16). The primary outcomes were change in total HCV‐RNA, LVP and ALT at week 12 compared with baseline. Secondary outcome was change in interferon‐gamma‐inducible protein‐10 (IP10) as a measure of interferon activation. Results 35% had compensated cirrhosis and 45% were prior null responders. There was no significant change in total HCV RNA, LVP, non‐LVP or LVP ratio in patients receiving fluvastatin or n‐3 PUFAs. ALT was not significantly different in those treated with fluvastatin or n‐3 PUFAs. 12 weeks of low‐dose n‐3 PUFA decreased median IP10 concentration by −39 pg/ml (−111, 7.0 pg/ml Q1–Q3). Conclusions Fluvastatin and n‐3 PUFAs have no effect on plasma HCV‐RNA or LVP. The effect of low‐dose n‐3 PUFA on IP10 warrants further prospective evaluation as a supplemental therapy to enhance interferon sensitivity.